Additional Evidenceon Ems Interest Rate Linkages - Thornton, John (IMF Working Papers; Working Paper, 1996)
This note examines interest rate linkages within the EMS. Cointegration tests suggest the existence of a long-run equilibrium relationship between German and other EMS interest rates. Bivariate VAR analysis finds that Granger-causality either stems from German to other European interest rates (Belgium, France, Spain, and the U.K.) or is bidirectional (Denmark and the Netherlands). When allowance is made for the influence of U.S. interest rates, the pattern of Granger causality is predominantly bidirectional.